Fallout from Jakarta's Monas incident: what is to be done with fringe groups? - Fatima Astuti (2016)
The recent clash between a hardline Muslim group and an alliance of organisations supporting the freedom of faith has led the government to consider using an old law to freeze the Islamic Defenders Front (FPI). This resort to a relic from Indonesia’s undemocratic past might be counter productive for Indonesian democracy in the future.